Aquaculture practices in irrigation reservoirs of the Western Cape Province of South Africa in relation to multiple resource use and socio-ecological interaction - Salie, Khalid (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.